An Industrial systems design study on Almazora Motors Corporation - Cruz, Jay Ferdinand V.; Dysangco, Ramon Luis Osmundo G.; Oloan, Hadjibar Vincent P.; Santos, Karl Antoni P. (College of Engineering, 2001)
The proponents of the study have conducted an Industrial Systems Design Study on Almazora Motors Corporation (AMC), an All-Utility Vehicle (AUV) body Manufacturer. AMC, having started at 1940, has been around for more than half a century. The company's first product line was the calesa. Then the company shifted to the manufacturing of passenger bus bodies, and in 1994 started the production of AUV bodies. The study covered areas concerned in Industrial Systems Design, which includes supply chain management and processes involved from the company's purchasing to distribution. The study is limited to the production of the company's AUV (All-Utility Vehicles) bodies, and will not cover their production of passenger bus bodies. This is due to the fact that the us Division Plant output is only 5 units a week as compared to the AUV Division Plant output of 20 units per week, making it more suitable for study. Initial data gathering, such as company profile, product lines, and the company's suppliers and distributors, was accomplished through preliminary interviews of key personnel. Through close coordination with purchasing personnel, the group evaluated their current supply chain system. All forms of assistance that the management extended to the group concerning past and present problems were incorporated in the study. Once the appropriate data was gathered, the group made use of the concepts, tools, current practices, and innovative ideas discussed in class in order to evaluate the current situation of the company. Further analyses were carried out through findings resulting from the evaluation of the company's suppliers as well as current market situation. Each of the concerns discussed in the study were addressed with different actions or plans generated by the group. The planned actions were elaborately discussed including their respective advantages and disadvantages. These are then evaluated to determine which of the actions should be implemented based on different criteria. Ratings under each criterion were set to be from 0 to 10, 10 being the highest. The alternatives were rated relative to each other and how they all fare on particular criteria. After careful evaluation of all the factors affecting the feasibility of projects, the group recommends the following alternatives for the further improvement of the company's operations: the implementation of a supplier selection criteria and method, implementation of a supplier assessment program, implementation of the ABC classification of inventories, the creation of a worker motivation program, the widening of the existing distances between machines, installation of an Electronic Data Interchange (EDI) incorporated with decentralized warehousing, and the creation of a full-pledged purchasing department. From the said recommendations, the group came up with an implementation strategy to help transform these recommendations into actions. The group intended to make recommendations as specific, yet flexible enough, as possible, attempting to address each determined problem area on a one-to-one basis. All data essential for documentation and analyses, as well as the group's findings and recommendations, were presented properly in the study. The group provided adequate explanations and justifications regarding the advantages and practicality of all the recommendations.